VALUASI EKONOMI WISATA ALAM DANAU LINOW TOMOHON BERDASARKAN BIAYA PERJALANAN WISATAWAN LOKAL - Enricco R. Kumesan; Welson M. Wangke; Gene H.M. Kapantow; Melissa L.G. Tarore (Universitas Sam Ratulangi, 2015)
ABSTRACT The aim of this research is to know the economic value of Linow Lake, a natural tourism destination in Tomohon, based on the travel cost method. The study conducted for five months starting from December 2014 until April 2015. The data used in this research were both primary data obtained from questionnaires filled by the respondents and secondary data collected from several relevant sources including managers from Linow Lake Tourism Management and officials from tourism officee of Tomohon City. Data were analyzed using the travel cost approach. The result showed that the travel cost significantly influenced the number of tourists visiting the lake. Moreover, the economic value based on the willingness to pay was Rp 244,549,550.40 by 1000 population or Rp 167,917.21 individually. The real cost spent by local tourists was Rp 196,098,922.26 by 1000 population or Rp 134,649,13 individually meaning that the consumer surplus was Rp 48,450,628.14 by 1000 population or Rp 33,268.08 individually. Key words:Economic valuation. Travel cost, Linow Lake Tomohon